The Effect of the Number of Elements on Leakage Currents in Iced String Insulators - Ozkucuk, Muhammed Bugracan; Gencoglu, Muhsin Tunay (Institute of Electrical and Electronics Engineers Inc., 2024)
String insulators are of critical importance for the insulation and safety of electrical transmission and distribution lines. In regions where winter conditions are intense, the icing factor negatively affects the performance of string insulators. Icing reduces the resistance of the insulator surface and reduces the insulation property, resulting in an increase in leakage currents. This situation poses a danger for the continuity of transmission and distribution lines by causing insulator damage. In this study, the analysis of leakage currents of iced porcelain string insulators according to the number of elements was performed. An alternating voltage of 20 kV was applied to the iced string insulators; leakage currents were obtained with the help of the LabVIEW program, and the effect of the number of elements of the string insulator on leakage currents was compared using experimental data. The relationship between the number of elements of the insulators and the number of leakage current pulses was examined. © 2024 IEEE.
Buzlu Zincir İzolatörlerde Eleman Sayisinin Kaçak Akimlar Üzerindeki Etkisi
2024 Electrical, Electronics and Biomedical Engineering Conference at 15th National Conference on Electrical and Electronics Engineering, ELECO 2024 -- 28 November 2024 through 30 November 2024 -- Bursa -- 206315
Keywords: Electric insulation; Electric insulators; Electric lines; Leakage (fluid); Porcelain; Potassium alloys; Problem oriented languages; 'current; Distribution lines; Electrical transmission and distributions; Insulation property; Insulator surfaces; Performance; String insulators; Transmission and distribution; Transmission-line; Winter conditions; Leakage currents